PERAN STRATEGIS SURIAH DALAM KONFLIK ARAB-ISRAEL TERHADAP LEGITIMASI PRESIDEN BASHAR AL-ASSAD - Windratmo Suwarno (Arabic Literature Department, 2013)
Unrest happening in Syria to make a democratic country is difficult to achievebecause there is a political interest of US and its allies. Syria has a strategic role ininfluencing political constellation in Middle East especially in Arab-Israeli conflict.Syrian partnership with Iran and her influence on resistence movement of Hezbollah inLebanon is a main factor to change Bashar regime. Political legitimate of Bashar regimewill hitherto not be fundamental issues in Syrian internal affairs due to the support ofallied countries to Syria. As long as the allied countries continue their supports to Syria,the regime will survive and the unrest will not an end.